Information Services for the Use of Mind Maps in Teaching: the Experience of University Experimental Work - Faizovna Azmetova, Rezeda (2021)
The purpose of the article is to identify the information services for creating mind maps in the process of linguistic training of future philologists at the seminars. A comparative analysis of the most used software products for creating mind maps was carried out based on an expert survey. The results of this analysis made it possible to choose a software product using mind maps. The results of the pedagogical experiment confirmed the assumption that mind maps are an effective means of mastering the knowledge of future philologists at the seminars. The use of mind maps in the processes of understanding information in the classroom affects the activity of students' listening, makes it possible to systematize information through personal understanding and structuring, and promotes effective memorization. The next areas of scientific research on the presented problem are the analysis of the effectiveness of mind maps in the independent work of students.